A high performance nickel-based welding rod and preparation method thereof

By using adhesives with modified montmorillonite and other components in the nickel-based electrodes, the existing nickel-based electrodes have poor arc stability, easy peeling of the powder skin and poor mechanical properties, and the welding process has been achieved Excellent, high mechanical properties and low temperature toughness effects.

CN119016938BActive Publication Date: 2025-02-25HUNAN XIANGGONG ENVIRONMENTAL PROTECTION SCI & TECH +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411431825.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-02-25
Estimated Expiration
2044-10-14

AI Technical Summary

Technical Problem

During welding, existing nickel-based electrodes have problems such as poor arc stability, easy peeling of the powder skin, and poor mechanical properties of the weld metal, which affects the performance of the electrode.

Method used

Use binders with modified montmorillonite and other components to improve the coating of nickel-based electrodes, including modified montmorillonite, β-cyclodextrin, sodium dodecanoate, potassium sodium water glass, calcium alginate, sodium chloride and water, improve the strength and welding performance of the skin through a specific preparation process.

Benefits of technology

It improves the strength of the nickel-based electrodes during welding, arc stability and weld forming aesthetics, and enhances the mechanical properties and low-temperature toughness of the clad metal.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005083876060000081
    Figure BDA0005083876060000081
  • Figure BDA0005083876060000091
    Figure BDA0005083876060000091
Patent Text Reader

Abstract

The present invention relates to the field of metal welding technology, and in particular to a high-performance nickel-based welding rod and a preparation method thereof. The high-performance nickel-based welding rod comprises a welding core and a coating covering the welding core, wherein the coating is composed of powder and a binder, and the binder comprises the following components in parts by weight: 10-18 parts of modified montmorillonite, 5-10 parts of β-cyclodextrin, 3-8 parts of sodium dodecanoate, 20-30 parts of potassium sodium water glass, 1-5 parts of calcium alginate, 3-6 parts of sodium chloride, and 1-3 parts of water. The nickel-based welding rod prepared by the present invention has high coating strength, stable arc, and less spatter during welding; excellent welding process, good slag removal, and beautiful weld formation; high mechanical properties and low-temperature toughness of the cladding metal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal welding, and in particular to a high-performance nickel-based welding rod and a preparation method thereof. Background Art

[0002] With the development of industry, new requirements have been put forward for material performance. In order to meet the use under various complex conditions, the research and development of new materials have attracted great attention from scholars. The corresponding welding materials have been rapidly developed. The most widely used new welding materials are stainless steel welding materials and nickel-based alloy welding materials.

[0003] Nickel-based alloy welding materials are alloy welding materials with nickel as the main component. Studies have found that nickel-based alloy welding materials are excellent corrosion-resistant materials that are most adaptable to various complex environments (such as high temperature, high pressure, and high chemical concentration), making them have broad application prospects in the fields of nuclear power, papermaking, petrochemicals, and marine engineering. However, some existing nickel-based alloy welding rods have technical problems such as poor arc stability, easy detachment of the coating, and poor mechanical properties of the weld metal during welding, which in turn affect the performance of the welding rod. Therefore, it is necessary to improve the performance of nickel-based welding rods. Summary of the invention

[0004] In order to overcome the deficiencies of the prior art, the first object of the present invention is to provide a high-performance nickel-based welding rod having excellent mechanical properties and low-temperature toughness.

[0005] The second object of the present invention is to provide a method for preparing a high-performance nickel-based welding rod with simple steps.

[0006] The first object of the present invention is achieved by the following technical solution:

[0007] A high-performance nickel-based welding rod, comprising a welding core and a coating covering the welding core, wherein the coating is composed of powder and a binder, and the binder comprises the following components in parts by weight: 10-18 parts of modified montmorillonite, 5-10 parts of β-cyclodextrin, 3-8 parts of sodium dodecanoate, 20-30 parts of potassium sodium water glass, 1-5 parts of calcium alginate, 3-6 parts of sodium chloride, and 1-3 parts of water;

[0008] Wherein, the preparation process of the modified montmorillonite is as follows:

[0009] (1) adding montmorillonite to an acidic solution, heating and stirring, discharging the material, and washing with water until neutral;

[0010] (2) calcining the montmorillonite treated in step (1) for later use;

[0011] (3) adding the montmorillonite and paper mulberry bark pulp calcined in step (2) into water to obtain a dispersion; adding a surfactant to the dispersion, heating and stirring, and purifying to obtain modified montmorillonite.

[0012] Furthermore, in step (1), the solid-liquid ratio of the montmorillonite and the acidic solution is 1 g:(10-12) mL, the acidic solution is a hydrochloric acid solution with a mass concentration of 5-10%, the heating temperature is 90-100° C., and the stirring time is 4-6 h.

[0013] Furthermore, the calcination temperature in step (2) is 350-450° C. and the calcination time is 2-3 h.

[0014] Furthermore, in step (3), the heating temperature is 60-70° C., the stirring time is 4-6 hours, the concentration of the calcined montmorillonite in the dispersion is 5-10wt%, and the concentration of the paper mulberry bark pulp in the dispersion is 1-3wt%.

[0015] Furthermore, the surfactant in step (3) is N,N-dimethyldodecylamine, and the mass of the added surfactant is 1-5% of the mass of the calcined montmorillonite.

[0016] Furthermore, the Baume degree of the potassium-sodium water glass is 40°-42°Bé.

[0017] Furthermore, the components of the powder include the following ingredients by weight: 25-30 parts of sodium fluoride, 2-5 parts of nickel powder, 6-12 parts of titanium oxide, 5-10 parts of natural wollastonite, 0.5-2 parts of ferrosilicon, 20-28 parts of metallic chromium, 1-6 parts of ferroniobium, 1-5 parts of mica, 0.5-2 parts of soda ash, 1-2 parts of ferromolybdenum, and 10-13 parts of barium carbonate.

[0018] The second object of the present invention is achieved by the following technical solution:

[0019] The method for preparing the above-mentioned high-performance nickel-based welding rod comprises the following steps:

[0020] The raw materials of the powder are mixed evenly according to the weight ratio to obtain a mixed powder, a binder is added to the mixed powder, and after stirring evenly, a coating is obtained, the coating is coated on the surface of the welding core, and the welding rod is obtained after drying.

[0021] Furthermore, the added amount of the binder is 15-20% of the total mass of the coating, and the mass of the coating in the welding rod is 25-35% of the total mass of the welding rod.

[0022] Furthermore, the drying temperature is 350-400° C. and the drying time is 2-3 hours.

[0023] Furthermore, the welding core is made of the following components: Cr 16-20%, Fe 5-7%, C 0.01-0.05%, Si0.01-0.05%, Mo 0.5%-1%, Co 1-2%, B≤0.002%, S≤0.004%, Mn≤0.5%, (Nb+Ta)≤0.05%, Ti 1.8-2.2%, and the balance is Ni.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The present invention improves the binder component in the coating of the nickel-based welding rod, and adds modified montmorillonite and other components. The performance of the nickel-based welding rod prepared by using the above binder is tested. The nickel-based welding rod prepared by the present invention has high coating strength, stable arc, less spatter during welding; excellent welding process, good slag removal, and beautiful weld formation; the mechanical properties and low-temperature toughness of the cladding metal are relatively high. DETAILED DESCRIPTION

[0026] The technical scheme of the present invention is further explained below in conjunction with specific examples and comparative examples. In the following examples and comparative examples, the raw materials and preparation methods used are conventional materials and techniques in the art unless otherwise specified.

[0027] (I) Embodiment

[0028] Example 1

[0029] Embodiment 1 provides a high-performance nickel-based welding rod, including a welding core and a coating covering the welding core, wherein the coating is composed of powder and a binder.

[0030] The binder is composed of the following components in parts by weight: 15 parts of modified montmorillonite, 6 parts of β-cyclodextrin, 7 parts of sodium dodecanoate, 23 parts of potassium sodium water glass, 2 parts of calcium alginate, 5 parts of sodium chloride, and 2 parts of water. The Baume degree of the potassium sodium water glass is 40°-42°Bé.

[0031] The specific preparation process of the modified montmorillonite is as follows:

[0032] (1) Add montmorillonite to 7% hydrochloric acid solution at a solid-liquid ratio of 1 g:12 mL, stir at 95 °C for 5 h, discharge, and wash with pure water until neutral;

[0033] (2) transferring the montmorillonite treated in step (1) to a tube furnace, raising the temperature of the tube furnace to 400° C., calcining for 2.5 h under nitrogen protection, and setting aside;

[0034] (3) The montmorillonite and paper mulberry bark pulp calcined in step (2) are added into water to obtain a dispersion, wherein the concentration of the calcined montmorillonite in the dispersion is 7wt%, and the concentration of the paper mulberry bark pulp in the dispersion is 2wt%. N,N-dimethyldodecylamine is then added, and the mass of the surfactant added is 3% of the mass of the calcined montmorillonite. The mixture is stirred at 65°C for 5h, and the solid material is collected, washed, and vacuum dried to obtain modified montmorillonite.

[0035] The specific preparation process of the paper mulberry bark pulp is as follows:

[0036] Clean the paper mulberry bark and cut it into segments of 2-4 mm. Place the paper mulberry bark segments in a NaOH solution (mass concentration of 12%), with the mass percentage of the paper mulberry bark segments in the solution being 7%. Soak at 95°C for 58 min, remove the NaOH solution, wash with water until neutral, then add a 2% NaOH solution and a 7% H2O2 solution with the mass percentage of the paper mulberry bark segments in the solution being 2%. Soak at 82°C for 40 min, remove the solution, wash with water until neutral, and extrude with a twin-screw extruder to make pulp (screw speed of 12r / min, pressure of 3MPa).

[0037] The components of the powder are, by weight, 27 parts of sodium fluoride, 4 parts of nickel powder, 10 parts of titanium oxide, 8 parts of natural wollastonite, 1 part of ferrosilicon, 25 parts of metallic chromium, 4 parts of ferroniobium, 3 parts of mica, 1.5 parts of soda ash, 1.5 parts of ferromolybdenum, and 12 parts of barium carbonate.

[0038] The welding core is made of the following composition: Cr 18%, Fe 6%, C 0.03%, Si 0.02%, Mo 0.8%, Co1.5%, B 0.001%, S 0.002%, Mn 0.1%, (Nb+Ta) 0.03%, Ti 2%, and the balance is Ni.

[0039] Embodiment 1 also provides a method for preparing a high-performance nickel-based welding rod, and the specific preparation process is as follows:

[0040] The raw materials of the powder are mixed evenly according to the weight ratio to obtain a mixed powder, and a binder is added to the mixed powder, the added amount of the binder is 18% of the total mass of the coating, and after stirring evenly, a coating is obtained, and the coating is coated on the surface of the welding core. After drying at 380°C for 2.5 hours, the above-mentioned welding rod is obtained, and the mass of the coating in the welding rod is 30% of the total mass of the welding rod.

[0041] Example 2

[0042] Embodiment 2 provides a high-performance nickel-based welding rod, including a welding core and a coating covering the welding core, wherein the coating is composed of powder and a binder.

[0043] The binder is composed of the following components in parts by weight: 10 parts of modified montmorillonite, 5 parts of β-cyclodextrin, 8 parts of sodium dodecanoate, 20 parts of potassium sodium water glass, 1 part of calcium alginate, 3 parts of sodium chloride, and 3 parts of water. The Baume degree of the potassium sodium water glass is 40°-42°Bé.

[0044] The specific preparation process of the modified montmorillonite is as follows:

[0045] (1) Add montmorillonite to 5% hydrochloric acid solution at a solid-liquid ratio of 1 g:10 mL, stir at 90°C for 6 h, discharge, and wash with pure water until neutral;

[0046] (2) transferring the montmorillonite treated in step (1) to a tube furnace, raising the temperature of the tube furnace to 350° C., calcining for 3 h under nitrogen protection, and setting aside;

[0047] (3) The montmorillonite and paper mulberry bark pulp calcined in step (2) are added into water to obtain a dispersion, wherein the concentration of the calcined montmorillonite in the dispersion is 5wt%, and the concentration of the paper mulberry bark pulp in the dispersion is 3wt%. N,N-dimethyldodecylamine is then added, and the mass of the surfactant added is 1% of the mass of the calcined montmorillonite. The mixture is stirred at 70°C for 4h, and the solid material is collected, washed, and vacuum dried to obtain modified montmorillonite.

[0048] The preparation method of paper mulberry bark pulp is the same as that in Example 1.

[0049] The components of the powder are, by weight, 25 parts of sodium fluoride, 2 parts of nickel powder, 6 parts of titanium oxide, 5 parts of natural wollastonite, 0.5 parts of ferrosilicon, 20 parts of metallic chromium, 1 part of ferroniobium, 1 part of mica, 0.5 parts of soda ash, 1 part of ferromolybdenum, and 10 parts of barium carbonate.

[0050] The welding core is made of the following composition: Cr 16%, Fe 7%, C 0.01%, Si 0.05%, Mo 1%, Co 2%, B0.002%, S 0.004%, Mn 0.5%, (Nb+Ta) 0.04%, Ti 2.2%, and the balance is Ni.

[0051] Embodiment 2 also provides a method for preparing a high-performance nickel-based welding rod, and the specific preparation process is as follows:

[0052] The raw materials of the powder are mixed evenly according to the weight ratio to obtain a mixed powder, and a binder is added to the mixed powder, the added amount of the binder is 15% of the total mass of the coating, and after stirring evenly, a coating is obtained, and the coating is coated on the surface of the welding core. After drying at 350°C for 3h, the above-mentioned welding rod is obtained, and the mass of the coating in the welding rod is 25% of the total mass of the welding rod.

[0053] Example 3

[0054] Embodiment 3 provides a high-performance nickel-based welding rod, including a welding core and a coating covering the welding core, wherein the coating is composed of powder and a binder.

[0055] The binder is composed of the following components in parts by weight: 18 parts of modified montmorillonite, 10 parts of β-cyclodextrin, 3 parts of sodium dodecanoate, 30 parts of potassium sodium water glass, 5 parts of calcium alginate, 6 parts of sodium chloride, and 1 part of water. The Baume degree of the potassium sodium water glass is 40°-42°Bé.

[0056] The specific preparation process of the modified montmorillonite is as follows:

[0057] (1) Add montmorillonite to 10% hydrochloric acid solution at a solid-liquid ratio of 1 g:11 mL, stir at 100 °C for 4 h, discharge, and wash with pure water until neutral;

[0058] (2) transferring the montmorillonite treated in step (1) to a tube furnace, raising the temperature of the tube furnace to 450° C., calcining for 2 h under nitrogen protection, and setting aside;

[0059] (3) The montmorillonite and paper mulberry bark pulp calcined in step (2) are added into water to obtain a dispersion, wherein the concentration of the calcined montmorillonite in the dispersion is 10wt%, and the concentration of the paper mulberry bark pulp in the dispersion is 1wt%. N,N-dimethyldodecylamine is then added, and the mass of the surfactant added is 5% of the mass of the calcined montmorillonite. The mixture is stirred at 60°C for 6h, and the solid material is collected, washed, and vacuum-dried to obtain modified montmorillonite.

[0060] The preparation method of paper mulberry bark pulp is the same as that in Example 1.

[0061] The components of the powder are, by weight, 30 parts of sodium fluoride, 5 parts of nickel powder, 12 parts of titanium oxide, 10 parts of natural wollastonite, 2 parts of ferrosilicon, 28 parts of metallic chromium, 6 parts of ferroniobium, 5 parts of mica, 2 parts of soda ash, 2 parts of ferromolybdenum, and 13 parts of barium carbonate.

[0062] The welding core is made of the following composition: Cr 20%, Fe 5%, C 0.05%, Si 0.01%, Mo 0.5%, Co1%, B0.002%, S 0.003%, Mn 0.2%, (Nb+Ta) 0.05%, Ti 1.8%, and the balance is Ni.

[0063] Embodiment 3 also provides a method for preparing a high-performance nickel-based welding rod, and the specific preparation process is as follows:

[0064] The raw materials of the powder are mixed evenly according to the weight ratio to obtain a mixed powder, and a binder is added to the mixed powder, the added amount of the binder is 20% of the total mass of the coating, and after stirring evenly, a coating is obtained, and the coating is coated on the surface of the welding core. After drying at 400°C for 2h, the above-mentioned welding rod is obtained, and the mass of the coating in the welding rod is 35% of the total mass of the welding rod.

[0065] (II) Comparative Example

[0066] Comparative Example 1

[0067] Comparative Example 1 provides a nickel-based welding rod, which is different from Example 1 in that:

[0068] The binder is composed of the following components in parts by weight: 15 parts of montmorillonite, 6 parts of β-cyclodextrin, 7 parts of sodium dodecanoate, 23 parts of potassium sodium water glass, 2 parts of calcium alginate, 5 parts of sodium chloride, and 2 parts of water, wherein the Baume degree of the potassium sodium water glass is 40°-42°Bé. The rest is the same as in Example 1.

[0069] Comparative Example 2

[0070] Comparative Example 2 provides a nickel-based welding rod, which is different from Example 1 in that:

[0071] The binder is composed of the following components in parts by weight: 12 parts of montmorillonite, 3 parts of paper mulberry bark pulp, 6 parts of β-cyclodextrin, 7 parts of sodium dodecanoate, 23 parts of potassium sodium water glass, 2 parts of calcium alginate, 5 parts of sodium chloride, and 2 parts of water, wherein the Baume degree of the potassium sodium water glass is 40°-42°Bé. The rest is the same as in Example 1.

[0072] Comparative Example 3

[0073] Comparative Example 3 provides a nickel-based welding rod, which is different from Example 1 in that:

[0074] The specific preparation process of modified montmorillonite is:

[0075] (1) Add montmorillonite to 7% hydrochloric acid solution at a solid-liquid ratio of 1 g:12 mL, stir at 95 °C for 5 h, discharge, and wash with pure water until neutral;

[0076] (2) transferring the montmorillonite treated in step (1) to a tube furnace, raising the temperature of the tube furnace to 400° C., calcining for 2.5 h under nitrogen protection, and setting aside;

[0077] (3) The montmorillonite calcined in step (2) is added into water to obtain a dispersion, wherein the concentration of the calcined montmorillonite in the dispersion is 7 wt %, and then N,N-dimethyldodecylamine is added, wherein the mass of the surfactant added is 3% of the mass of the calcined montmorillonite, and the mixture is stirred at 65° C. for 5 h, and the solid material is collected, washed, and vacuum dried to obtain modified montmorillonite. The rest is the same as in Example 1.

[0078] The properties of the nickel-based welding rods prepared in Examples 1-3 and Comparative Examples 1-3 are tested below.

[0079] The nickel-based electrodes prepared in Examples 1-3 and Comparative Examples 1-3 were used to perform corresponding welding on 9Ni steel, and the welding process parameters were: current 110-130A, interpass temperature controlled at 120-130°C, and number of layers 6-8.

[0080] (1) Process performance: The welding process record is shown in Table 1.

[0081] (2) Mechanical properties: After welding, the yield strength, tensile strength, elongation after fracture and -196°C impact properties of each group of deposited metals were tested in accordance with GB / T2652-2008 "Tensile test methods for welds and deposited metals". The results are shown in Table 2-3.

[0082] Table 1

[0083]

[0084]

[0085] Table 2

[0086] Group Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Yield strength(MPa) 467 456 443 365 411 398 Tensile strength(MPa) 731 724 710 631 683 660 Elongation(%) 35 32 30 24 27 26

[0087] Table 3

[0088] Group / Shock value(J) Weld center Weld Line Fusion line +2mm Example 1 92 85 103 Example 2 88 83 100 Example 3 86 80 95 Comparative Example 1 64 60 76 Comparative Example 2 75 72 87 Comparative Example 3 70 68 83

[0089] It can be seen from Tables 1-3 that when the nickel-based welding rods prepared in Examples 1-3 of the present invention are used for welding, there is no reddening and cracking of the coating, and the weld formation is good; in addition, the nickel-based welding rods also have excellent mechanical properties and low-temperature toughness. The above results show that the nickel-based welding rods prepared in the present invention have good welding process and excellent mechanical properties and low-temperature toughness.

[0090] Compared with Examples 1-3, the nickel-based welding rods prepared in Comparative Examples 1-3 have red coating and cracking phenomena during welding, and the weld formation is poor; in addition, the mechanical properties and low-temperature toughness of the nickel-based welding rods are poor. This is because the modified montmorillonite prepared in the present invention is not used in the preparation of nickel-based welding rods in Comparative Examples 1-3. It can be seen from the above that the modified montmorillonite prepared in the present invention can enhance the strength of the coating, improve the arc stability, and thus enhance the mechanical properties of the welding rod.

[0091] In summary, the nickel-based welding rod prepared by the present invention has high coating strength, stable arc and less spatter during welding; excellent welding process, good slag removal and beautiful weld formation; the mechanical properties and low-temperature toughness of the cladding metal are relatively high.

[0092] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.

Claims

1. A high performance nickel-based welding rod, characterized in that: The invention comprises a welding core and a coating covering the welding core, wherein the coating is composed of a drug powder and a binder, and the binder comprises the following components in parts by weight: 10-18 parts of modified montmorillonite, 5-10 parts of β-cyclodextrin, 3-8 parts of sodium dodecanoate, 20-30 parts of potassium sodium water glass, 1-5 parts of calcium alginate, 3-6 parts of sodium chloride, and 1-3 parts of water; Wherein, the preparation process of the modified montmorillonite is as follows: (1) adding montmorillonite to an acidic solution, heating and stirring, discharging the material, and washing with water until neutral; (2) calcining the montmorillonite treated in step (1) for later use; (3) adding the montmorillonite and paper mulberry bark pulp calcined in step (2) into water to obtain a dispersion; adding a surfactant to the dispersion, heating and stirring, and purifying to obtain modified montmorillonite.

2. The high performance nickel-based welding rod according to claim 1, characterized in that: In step (1), the solid-liquid ratio of montmorillonite and acidic solution is 1g:(10-12)mL, the acidic solution is a hydrochloric acid solution with a mass concentration of 5-10%, the heating temperature is 90-100°C, and the stirring time is 4-6h.

3. The high performance nickel-based welding rod according to claim 1, characterized in that: The calcination temperature in step (2) is 350-450° C. and the calcination time is 2-3 hours.

4. The high performance nickel-based welding rod according to claim 1, characterized in that: In step (3), the heating temperature is 60-70° C., the stirring time is 4-6 hours, the concentration of the calcined montmorillonite in water is 5-10wt%, and the concentration of the paper mulberry bark pulp in water is 1-3wt%.

5. The high performance nickel-based welding rod according to claim 1, characterized in that: The surfactant in step (3) is N,N-dimethyldodecylamine, and the mass of the added surfactant is 1-5% of the mass of the calcined montmorillonite.

6. The high performance nickel-based welding rod according to claim 1, characterized in that: The Baume degree of the potassium-sodium water glass is 40°-42°Bé.

7. The high performance nickel-based welding rod according to claim 1, characterized in that: The components of the powder are measured by weight and include the following ingredients: 25-30 parts of sodium fluoride, 2-5 parts of nickel powder, 6-12 parts of titanium oxide, 5-10 parts of natural wollastonite, 0.5-2 parts of ferrosilicon, 20-28 parts of metallic chromium, 1-6 parts of ferroniobium, 1-5 parts of mica, 0.5-2 parts of soda ash, 1-2 parts of ferromolybdenum, and 10-13 parts of barium carbonate.

8. The method for preparing a high-performance nickel-based welding rod according to any one of claims 1 to 7, characterized in that: The following steps are involved: The raw materials of the powder are mixed evenly according to the weight ratio to obtain a mixed powder, a binder is added to the mixed powder, and after stirring evenly, a coating is obtained, the coating is coated on the surface of the welding core, and the welding rod is obtained after drying.

9. The method for preparing a high-performance nickel-based welding rod according to claim 8, characterized in that: The added amount of the binder is 15-20% of the total mass of the coating, and the mass of the coating in the welding rod is 25-35% of the total mass of the welding rod.

10. The method for preparing a high performance nickel-based welding rod according to claim 8, characterized in that: The drying temperature is 350-400° C. and the drying time is 2-3 hours.

Citation Information

Patent Citations

  • Nickel-chromium-iron alloy steel nickel base welding rod used for war industry pneumatic system and production method of nickel-chromium-iron alloy steel nickel base welding rod

    CN106112312A

  • Low-grade attapulgite welding rod and preparing method thereof

    CN106891108A